Managerial Reaction To Management By Objectives - Tosi, Henry L.; Carroll, Stephen J. (Academy of Management Journal, 1968)
Fifty managers were interviewed regarding their reactions toward management by objectives. While there were generally positive values associated with it, problems were uncovered which should serve as a caution for those intending to install it.